REFRAMING SHORT STORY WRITING INSTRUCTION IN INDONESIAN SENIOR HIGH SCHOOLS THROUGH 6C-BASED DIGITAL MATERIALS - Galih Ramadhan; Jaja; Yusida Gloriani (English Review: Journal of English Education, 2026)
This study aims to develop digital teaching materials for writing short stories based on 6C skills for high school students. 6C skills are 21st-century skills that include critical thinking, creativity, communication, collaboration, character, and citizenship skills developed through the learning process. The research method used is research and development (R&D) using the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The analysis stage is carried out through a study of the content of 6C skills in six short story texts as a basis for developing teaching materials. The developed digital teaching materials were then validated by validators who include material experts, language experts, digital media experts, and practicing teachers. The validation results show that the digital teaching materials based on 6C skills in learning to write short stories are very feasible. Implementation of the teaching materials was carried out on grade XI students at SMA Negeri 1 Kadugede and SMA Negeri 1 Kawali. The evaluation results showed an average classical learning completion rate in both schools of 92.32%, with an average score above 81. Analysis of students' short story texts showed that the 6C skills were contextually integrated, comprehensive, and evenly distributed in students' narrative construction. The integration was internalized in the interactions between characters, the context of social reality, character, creativity, and was reflective.